Role of granulocyte colony stimulating factor (G-CSF) in dengue patients with severe thrombocytopenia - Khan, Kamran Amir; Sameed Ullah Qureshi (Journal of the Pakistan Medical Association, 2024)
Objective: To determine the effects of granulocyte colony-stimulating factor in improving platelet count in patients with dengue fever. Method: The retrospective, cross-sectional study was conducted at Northwest General Hospital and Research Centre, Peshawar, Pakistan, between January 2021 and October 2022, and comprised dengue fever inpatients regardless of age and gender who received granulocyte colony-stimulating factor subcutaneously. The impact of colony-stimulating factor on platelet and white blood cell counts as well as any unfavourable consequences was assessed. Convenient sampling was used and a structured format was used for data collection. Data was analysed using SPSS 21. Results: Of the 100 patients, 67(67%) were males and 33(33%) were females. The largest age group was that of >55 years 31(31%), fever was present in all the 100(100%) cases, bleeding in 18(18%) and platelet count <30,000 in 83(83%) cases. Dengue fever was confirmed by rapid dengue nonstructural protein 1 antigen in 76(76%) cases, dengue immunoglobulin G antibody test 28(28%), and immunoglobulin M antibody test in 31(31%) cases. Overall, 72(72%) patients received only one dose of granulocyte colony-stimulating factor. Post-administration, a substantial rise in the median platelet and white blood cell counts was seen compared to the baseline (p<0.05) on day 2. Conclusion: Granulocyte colony-stimulating factor helped increase platelet and white blood cell counts quickly in dengue fever patients. Key Words: Granulocyte colony-stimulating factor, Dengue, Thrombocytopenia.